2014
DOI: 10.1177/1352458514533398
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for multiple sclerosis relapses after switching from natalizumab to fingolimod

Abstract: There was an increase of the ARR in the first year after switching from NAT to FTY. Last EDSS during the switching period was a predictor of relapses during FTY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 15 publications
4
30
1
6
Order By: Relevance
“…Based on this pharmacokinetic profile, NAT should be fully cleared from circulation approximately 2 months (5 half-lives) after the last dose13. According to this observation, we found that the mean time of the first relapse after NAT withdrawal was above 26 weeks, in line with the observations of Hoepner et al [14].…”
Section: Discussionsupporting
confidence: 93%
“…Based on this pharmacokinetic profile, NAT should be fully cleared from circulation approximately 2 months (5 half-lives) after the last dose13. According to this observation, we found that the mean time of the first relapse after NAT withdrawal was above 26 weeks, in line with the observations of Hoepner et al [14].…”
Section: Discussionsupporting
confidence: 93%
“…Disability and clinical course were also examined by Hoepner et collegues [11] in a smaller cohort of patients (n = 33) switching from natalizumab to fingolimod. The study found that 61% of patients relapsed after natalizumab discontinuation and 48% relapsed during fingolimod treatment (with a washout no longer than 24 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod (Gilenya, Novartis, Basel, Switzerland) is an option for these patients [1,3,[8][9][10][11][12] however, because of the still unknown impact on the immune system of the concomitant presence of these molecules, an interval is recommended between discontinuing natalizumab and starting fingolimod. Studies investigating switching from natalizumab to fingolimod have shown clinically relevant disease activity during the first weeks of fingolimod treatment, challenging its effectiveness in this setting, and highlighting the need to clarify its role in patients with a disease characterized by its severity and rapid evolution, and to improve the switching protocol [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obvious candidate in this situation appears to be fingolimod which was recently shown to be advantageous over injectables after cessation of natalizumab [98], but is probably clinically less potent than natalizumab. Furthermore, some recent data strongly suggest that a switch from natalizumab to fingolimod may be associated with an increased risk of developing new disease activity [99,100]. A recent report came to the conclusion that too-long washout phases between natalizumab discontinuation and fingolimod initiation may elevate that risk and recommends waiting 4-8 weeks between treatments [101].…”
Section: Switching Between Second-line Therapiesmentioning
confidence: 99%